(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aimed at determining the difficulties of applying active learning in the first cycle of basic education from the point of view of teachers and educational supervisors in light of the variables of years of experience and gender. To achieve this goal, The study tool was designed to identify the difficulties of applying active learning, consisting of (30) paragraphs, which were validated and validated, and distributed to the sample of the study. The most important results were that the level of difficulties in applying active learning in schools from the teachers’ perspective was moderate. The results showed that there is a statistically significant difference in the level of difficulty due to the gender variable and the female variable and the scientific qualification variable in favor of teachers who hold the diploma and postgraduate qualifications, Number of years for those with little educational experience.